1997
DOI: 10.1103/physreva.56.2477
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion cancellation and quantum eraser experiments analyzed in the Wigner function formalism

Abstract: We extend the Wigner function formalism for parametric down-conversion experiments presented in a previous paper ͓Phys. Rev. A 55 3879 ͑1997͔͒ to experiments involving propagation through a dispersive medium ͓Steinberg et al., Phys. Rev. A 45, 6659 ͑1992͔͒, and polarization ͓Kwiat et al., Phys. Rev. A 45, 7729 ͑1992͔͒. ͓S1050-2947͑97͒02009-X͔ PACS number͑s͒: 42.50.Ar, 03.65.Sq, 42.50.Lc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…A more ambitious program was started by a British-Spaniard group with the hope to build a real alternative to Quantum Optics [297,298,299,300,301,302,303]. The main idea was that the probability distribution for the hidden variable is given by the Wigner function, which is positive for photons experiments.…”
Section: Lhvt Built For Surviving Pdc Experimentsmentioning
confidence: 99%
“…A more ambitious program was started by a British-Spaniard group with the hope to build a real alternative to Quantum Optics [297,298,299,300,301,302,303]. The main idea was that the probability distribution for the hidden variable is given by the Wigner function, which is positive for photons experiments.…”
Section: Lhvt Built For Surviving Pdc Experimentsmentioning
confidence: 99%
“…Marshall's experimental suggestions involves work he has advanced with colleagues, particularly E. Santos, in "stochastic optics," aiming in particular at a local model explanation of the Bell inequalities [60], [61]. At the end of the 1990s, Marshall developed with colleagues a local physical explanation of entanglement involving a nonlinear optical process often called spontaneous parametric down conversion [62], [63], [64], [65], [66], [67]. This work led them to the prediction of a new phenomena, still to be tested for, involving a natural explanation in terms of unquantized light and local quantities that they have termed spontaneous parametric up conversion [68], [69], [70], [71].…”
Section: Physical Ideas Behind Sedmentioning
confidence: 99%
“…We show that entanglement, in the Wigner representation, is just a correlation that involves both signals and vacuum fluctuations. An analysis of the detection process opens the way to a complete description of parametric down conversion in terms of pure Maxwell electromagnetic waves.The theory of parametric down conversion (PDC) was treated, in the Wigner formalism, in an earlier series of articles [1,2,3]. There we showed that, provided one considers the zeropoint fluctuations of the vacuum to be real, the description of radiation is fully within Maxwell electromagnetic theory.…”
mentioning
confidence: 99%
“…The theory of parametric down conversion (PDC) was treated, in the Wigner formalism, in an earlier series of articles [1,2,3]. There we showed that, provided one considers the zeropoint fluctuations of the vacuum to be real, the description of radiation is fully within Maxwell electromagnetic theory.…”
mentioning
confidence: 99%